Retention Basin Water Quality in Tubuhue Urban Village North Central East Regency - Made Santiari; Yohana Ivana Kedang; Feliksitas Angel Masing (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2022)
The community carries out bathing and washing activities directly in the retention basin which can cause polluted water. Water quality checks need to be carried out before treatment. The purpose of this study was to determine the quality of water in the retention basin. Determination of the sampling location by purposive sampling. Sampling was carried out once in August 2021. Parameter measurements were carried out in the field and in the laboratory. The measurement results are compared with the quality standards listed in the Regulation of the Minister of Health of the Republic of Indonesia Number 32 of 2017 concerning Environmental Health Quality standards and Water Health Requirements for Sanitary Hygiene, Swimming Pools, Solus Per Aqua and Public Baths. A parameter that passed the quality standard was E-Coli while pH, hardness, nitrate, temperature, and TDS still met the quality standards. Retention basin water in Tubuhue Village seen from the parameters of temperature, pH, TDS, hardness, and nitrate can be used for sanitation hygiene purposes, but judging from the parameter E-Coli cannot be used for sanitary hygiene purposes.